Understanding Pacemaker-Induced Cardiomyopathy Incidence and Predictors in Patients with Right Ventricular Pacing: A Systematic Review - Laksono, Sidhi; Setianto, Budhi; Iqbal, Mohammad; Prawara, Ananta Siddhi (International Journal of Angiology, 2021)
This study aimed to figure out the incidence and predictors of pacemaker-induced cardiomyopathy (PICM) in patients with right ventricular (RV) pacing. We systematically searched in PubMed on March 18, 2020, for English language abstract and full-article journals, using the following criteria: pacemaker induced cardiomyopathy AND right ventricular AND pacemaker AND patients AND human NOT implantable cardioverter defibrillator NOT ICD NOT animal. Four studies were included in this review after filtering 35 studies through year of publication and abstract selection. The average PICM incidence from 1,365 patients included from the four studies was 10.7 to 13.7%. One study stated that preimplantation left ventricular ejection fraction (LVEF) was the predictor for the development of PICM. Three studies mentioned that RV pacing burden was the predictor for the development of PICM. However, the percentage differ in three studies: ≥20, >40, and 60%. In addition, one of the studies also included interventricular dyssynchrony as another predictor. The incidence of PICM in patients with RV pacing ranged from 10.7 to 13.7%. Preimplantation LVEF, interventricular dyssynchrony, and burden of RV pacing are reported as the predictors for the development of PICM in patients with RV pacing.
Keywords: heart pacing; cardiomyopathy; pacemaker